Marriott Hotels and the globalization of a brand - Gupta, Anil K. (Henry Stewart Talks, 2018)
This case study examines Marriott and the company’s strategy for globalisation. By focusing on globalising one brand, Ritz-Carlton, Marriott expanded quickly and Ritz-Carlton is now the global leader in the luxury hotel market. Focusing on Ritz-Carlton was the logical choice as the brand caters to a global customer base and the local adaptation imperatives are minimal.